Advances in catalysis and related subjects. - Frankenburg, Walter G., 1893-; Komarewsky, V. I. (Vasili Ilyich), 1895-; Rideal, Eric K. (Eric Keightley), Sir, 1890- (Advances in catalysis and related subjects, 1956)
ADVANCES IN CATALYSIS VOLUME 8.